Jobs or Privileges : Unleashing the Employment Potential of the Middle East and North Africa - World Bank (Washington, DC, 2014)
This report argues that Middle East and North Africa (MENA) countries face a critical choice in their quest for higher private sector growth and more jobs: promote competition, equal opportunities for all entrepreneurs and dismantle existing privileges to specific firms or risk perpetuating the current equilibrium of low job creation. The report shows that policies which lower competition in MENA also constrain private sector development and job creation. The report highlights the central role of promoting competition to stimulate private sector growth. However, there is little evidence on the political economy factors that perpetuate and or accentuate the lack of competition in the region, nor on the type of policy distortions that weaken competition and how those distortions ultimately affect job creation. This report aims to fill these gaps. It tackles the following questions: what types of firms create more jobs in MENA?; are they different from other regions?; what policies in MENA prevent the private sector from creating more jobs?; how do these policies affect competition and job creation?; and to what extent are these policies associated with privileges to politically connected firms? This report provides evidence that privileges granted to politically connected firms are associated with many of the policy distortions that the literature identifies to weaken private sector growth and job creation. This report assembles the most comprehensive firm census database ever put together for the MENA region. This allows to measure accurate characteristics of and trends in firms' demand for labor, and provides reliable representative estimates of both aggregate private sector job creation and productivity growth determinants. The report is organized in four chapters as follows: chapter one analyzes the dynamics and determinants of job creation and tests whether the fundamentals of job creation in MENA are similar to those in fast growing developing and high income countries. Chapter two shows how different policies in MENA countries shaped private sector competition and thus the firm dynamics associated with job growth identified in chapter one. Chapter three documents past industrial policies in MENA and compare the experiences in MENA with the experiences of East Asian countries, highlighting how the differences are linked to policy objective, design, and implementation. Chapter four analyzes how privileges to politically connected firms result in policy distortions that undermine competition and constrain private sector growth and jobs in MENA. The report concludes by laying out the implications for policy of the various findings and lays out the specific areas for policy reform to the roadmap for more private sector growth and jobs in MENA.